2023
DOI: 10.1002/adfm.202309701
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Electron Spin States of Na4Fe3(PO4)2P2O7 Cathodes via Mn/F Dual‐Doping for Enhanced Sodium Storage

Yukun Xi,
Xiaoxue Wang,
Hui Wang
et al.

Abstract: A NASICON‐type Mn/F dual‐doping Na4Fe3(PO4)2P2O7 cathode material is successfully synthesized via a spray drying method. A medium‐spin of Fe is measured by DFT calculation, X‐ray absorption near edge structure (XANES), temperature‐dependent magnetization susceptibility (M−T) measurement, and electron paramagnetic resonance (EPR) tests. It indicates that the eg orbital occupation of Fe2+ can be finely regulated, thus optimizing the bond strength between the oxidation and reduction processes. Furthermore, from U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The contributions of ion diffusion and pseudocapacitive diffusion at different scan rates ( v ) can be derived from eqn (8): i ( v ) = k 1 v + k 2 v 1/2 where k 1 v represents the contribution of pseudocapacitive diffusion, while k 2 v 1/2 represents the contribution of ion diffusion. 39,40 As depicted in Fig. 4C, the pseudo-capacitance contribution rate of Bi 2 Te 3 /rGO at 1 mV s −1 was determined to be 64% (blue region).…”
Section: Resultsmentioning
confidence: 88%
“…The contributions of ion diffusion and pseudocapacitive diffusion at different scan rates ( v ) can be derived from eqn (8): i ( v ) = k 1 v + k 2 v 1/2 where k 1 v represents the contribution of pseudocapacitive diffusion, while k 2 v 1/2 represents the contribution of ion diffusion. 39,40 As depicted in Fig. 4C, the pseudo-capacitance contribution rate of Bi 2 Te 3 /rGO at 1 mV s −1 was determined to be 64% (blue region).…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, altering the solvation capacity of the electrolyte, introducing reaction aids, or reducing the particle size to the nanoscale may reduce the challenges associated with ion transport and activation energy, thus effectively improving electrochemical kinetic processes. For example, the brilliant bonding properties can reduce the diffusion barrier for ions, hence accelerating reaction kinetics and electron/ion transport. , Consequently, sufficient electrochemical kinetics during ion insertion/extraction may promote the alloy of K with Sn, resulting in a higher capacity in KIBs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the brilliant bonding properties can reduce the diffusion barrier for ions, hence accelerating reaction kinetics and electron/ion transport. 39,40 Consequently, sufficient electrochemical kinetics during ion insertion/extraction may promote the alloy of K with Sn, resulting in a higher capacity in KIBs.…”
Section: Alkali-ion Intercalation and Structural Evolutionmentioning
confidence: 99%
“…The low cost, high stability, and wide distribution of feedstock costs offered by sodium-ion batteries (SIBs) make them well-suited for fulfilling the demands of large-scale electrochemical energy storage systems. However, SIBs still have great challenges; despite having the same working principle as lithium-ion batteries (LIBs), they are limited by the ionic radius (Na + : 1.02 Å; Li + : 0.76 Å), which leads to poor de-embedding capability. Therefore, there is a need to develop more suitable electrode materials to fulfill large-scale storage requirements. In recent years, there has been a progression in sodium-ion cathode materials, with the emergence of various materials including transition-metal oxides, polyanion materials, and Prussian analogues. Iron-based polyanion materials with low raw material cost, high thermal stability, and environmental friendliness have gained a lot of attention for their advantages. Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 (NFPP, theoretical capacity: 129 mA h g –1 ) was connected by combining [PO 4 ] and [P 2 O 7 ] groups with [FeO 6 ] octahedra, based on the redox Fe 2+ /Fe 3+ (average working voltage: 3.1 V), to realize the de-embedding of Na + in the cathode. Kim et al reported NFPP as a sodium-ion cathode material with a high reversible capacity of 113.5 mA h g –1 , marking the first discovery of such quality.…”
Section: Introductionmentioning
confidence: 99%